Impact of antenatal corticosteroids on head circumference of full‐term newborns: A French multicenter cohort study. (3rd April 2020) - Diguisto, Caroline; Arthuis, Chloé; Couderchet, Judith; Morgan, Andrei S.; Perrotin, Franck; Rivière, Olivier; Vendittelli, Françoise
Abstract: Introduction: Our main objective was to evaluate whether antenatal corticosteroids increase the risk of small head circumference in children born at term. Secondary objectives were to evaluate whether they increase the risk of small birthweight and birth length among those children. Material and methods: A historical cohort included 275 270 live term born children between 2000 and 2013 in 175 French maternity units. The rate of head circumference below the 5th percentile among children born at term and exposed to antenatal corticosteroids was compared with that of two unexposed groups: those children born at term whose mothers had an episode of threatened preterm labor without corticosteroids and those whose mothers had neither threatened preterm labor nor corticosteroids. The association between this treatment and head circumference was evaluated by calculating adjusted risk ratios (aRRs) and their 95% confidence intervals (CIs). The main outcome measure was a head circumference below the 5th percentile at birth, adjusted for sex, and gestational age according to the Pediatric, Obstetrics, and Gynecology Electronic Records Users Association (AUDIPOG) curves. Secondary outcomes were birthweight and birth length below the 5th percentile. Results: The rate of head circumference below the 5th percentile was 5.8% (n = 3388) among children exposed to antenatal corticosteroids and 4.3% (n = 7077) and 4.6% (n = 198 462), respectively, for the two unexposed groups. After adjustment, the risk of having a head circumference below the 5th percentile did not differ between the exposed group and the two control groups (aRR 1.28, 95% confidence interval [CI] 0.97‐1.69] and aRR 0.91, 95% CI 0.74‐1.13). We did not find an association between antenatal corticosteroids and the rate of birthweight below the 5th percentile. Children exposed to antenatal corticosteroids had a higher risk of a birth length below the 5th percentile when compared with those not exposed to threatened preterm labor or corticosteroids. Conclusions: We found no association between antenatal corticosteroids and increased risk of head circumference below the 5th percentile in children born at term.